(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The researchers chose this topic because they think many of the Filipinos know that the papaya fruit is a good source of vitamins like zinc and calcium and they want to prove that the papaya has a lot of vitamins that is why the researchers created a product that has a papaya jam inside so that even the younger people will enjoy it. The researcher used survey questionnaire because it is the easiest way to conduct a survey. The researchers found out that 7 out of 10 respondents chose the papaya over the squash. Therefore, the researchers concluded that many of the respondents want the product. The researchers concluded that papaya munckin and other flavour will be successful in the business industry. The researchers found out that this study will be successful according to respondents through survey questionnaire.